Monarchy . and, Three political letters. With an introd. by D. Nicholl and a note on the chronology of Dante's political works by C. Hardie. [Transl. by D. Nicholl and C. Hardie].; (London, 1954)
Library of ideas, eds I. Berlin, S. Hampshire and R. Wollheim.